John A. Liggat papers - Liggat, John A.
Account book kept by Liggat as trustee for Mary M. Brooks. Also includes account book, receipts, and note kept by Liggat for the estate of Alexander Liggat of Lynchburg, Va. Includes receipts for rent and expenditures for plantation and household maintenance and a reference (April 16, 1864) to Camp Lee, Richmond, Va.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brooks, Mary M; Liggat, Alexander -- Estate; Plantations -- Virginia; Lynchburg (Va.) -- History; Lynchburg (Va.) -- Social life and customs; Richmond (Va.) -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.